18F-FDG-PET brain imaging may highlight brain metabolic alterations in dysautonomic syndrome after human papilloma virus vaccination. Issue 12 (December 2020) - Vadalà, Maria; Cistaro, Angelina; Quartuccio, Natale; Calcagni, Maria Lucia; Fania, Piercarlo; Margotti, Simone; Schiera, Irene Giovanna; Laurino, Carmen; Palmieri, Beniamino
Abstract : Aim: The aim of this study was to evaluate brain glucose metabolism by means of [18F]-fluoro-deoxygluycose ( 18 F-FDG) PET in a group of patients presenting dysautonomic syndrome after human papilloma virus (HPV) immunization. Methods: Medical records of patients, referred to the 'Second Opinion Medical Consulting Network' Medical Centre (Modena, Italy) diagnosed with dysautonomic syndrome were searched. Inclusion criteria were presence in the medical history of adverse drug reactions following HPV vaccine; a Montreal Cognitive Assessment score <25 and good quality of a 18 F-FDG-PET brain scan performed within 12 months from the diagnosis of dysautonomic syndrome. 18 F-FDG-PET images of patients (HPV-group) were compared to a control group, matched for age and sex, using statistical parametric mapping (SPM). Results: The 18 F-FDG-PET study was available for five female patients. The SPM-group analysis revealed significant hypometabolism ( P < 0.05 false discovery rate corrected) in the right superior and medial temporal gyrus (Brodmann areas 22, 21) and insula (Brodmann area 13). At a threshold of P < 0.001 (uncorrected), further hypometabolic regions were revealed in the right superior temporal gyrus (Brodmann area 42) and caudate head and in the left superior temporal gyrus (Brodmann area 22), frontal subcallosal gyrus (Brodmann area 47) and insula (Brodmann area 13). Relative hypermetabolism ( P = 0.001) was revealed in the right premotor cortex (Brodmann area 6). Conclusion: This study revealed the possibility of altered brain glucose metabolism in subjects with dysautonomic syndrome post-immunization with HPV vaccine. These results could reinforce the hypothesis of a causal relationship between HPV vaccine, or some component included in the vaccine and the development of clinical manifestations.